Quantifiers, Questions and Quantum Physics
VI, 360 p.
Keywords: Jaakko Hintikka is one of the most creative figures in contemporary philosophy. He has made significant contributions to virtually all areas of the discipline, from epistemology and the philosophy of logic to the history of philosophy and the philosophy of science. Part of the fruitfulness of Hintikka’s work is due to its opening important new lines of investigation and new approaches to traditional philosophical problems. This volume gathers together essays from some of Hintikka’s colleagues and former students exploring his influence on their work and pursuing some of the insights that we have found in his work. This book includes a comprehensive overview of Hintikka’s philosophy by Dan Kolak and John Symons and an annotated bibliography of Hintikka’s work.